Intensitas Penyakit Busuk Pangkal Batang Pada Tanaman Lada (Piper nigrum L) Di Desa Batuah Kecamatan Loa Janan Kabupaten Kutai Kartanegara - Ni'matuljannah Akhsan; Albert Patangke (Agrifarm : Jurnal Ilmu Pertanian, 2019)
The Malonan-1 variety is a pepper plant originating from East Kalimantan which has become a national superior pepper. This pepper contains around 2,35% essential oil, oleoserin 11,23% and piperine 3,82% and tolerance to stem rot disease. Preliminary survey results in the village of Batuah, Kutai Kartanegara District, East Kalimantan, it was found that the stem rot disease in Malonan-1 pepper, therefore it is necessary to conduct research to find out how much the intensity of the stem rot disease at this time and identify fungi that cause stem rot rot disease in pepper plants. This research was conducted for 5 months starting from January to May 2019. The research location was in Batuah Village, Loa Janan Subdistrict, Kutai Kartanegara District and in the Plant Disease Pest Laboratory, Faculty of Agriculture, Mulawarman University. Research includes activities in the field and in the laboratory. The activity in the field is a direct survey of eight pepper farmer groups and calculating the intensity of the disease. Also carried out samples of symptomatic stem rot disease to be brought to the laboratory. Activities in the laboratory are the preparation of tools and materials to isolate samples of pepper plants. The isolated fungal colonies were purified and then idenfied and continued with Koch's postulate. The average intensity of stem rot disease at the current Lada plant in Batuah village is 14,58% (mild), the highest intensity in the Young Lada farmer group is 26,52% and the lowest intensity in the Beringin Jaya Farmer group is 4.3%. Based on the results of isolation, the root disease of the pepper plant (Piper nigrum L) in Batuah Village, Loa Janan District, Kutai Kartanegara Regency is Phytophthora capsici L.